DNA-fueled molecular machine for label-free and non-enzymatic ultrasensitive detection of telomerase activity. Issue 16 (13th July 2016) - Sun, Panpan; Ran, Xiang; Liu, Chaoqun; Liu, Chaoying; Pu, Fang; Ren, Jinsong; Qu, Xiaogang
Abstract : A label-free and non-enzymatic method based on DNA-fueled molecular machine has been introduced for ultrasensitive detection of telomerase activity in cancer cell extracts even at the single-cell level. Abstract : Herein, a non-enzymatic and label-free strategy based on DNA-fueled molecular machine was developed for ultrasensitive detection of telomerase activity in cancer cell extracts even at the single-cell level.